The Role of Justice Collaborators in Narcotics Crime Prosecution: Peran Saksi Pelaku yang Bekerja Sama dalam Penuntutan Tindak Pidana Narkotika - Silaban, Rizki; Poernomo, Gatoet (Universitas Muhammadiyah Sidoarjo, 2024)
This article examines the significance of Justice Collaborators in the legal process, particularly in narcotics cases. With the evolution of crime, especially organized narcotics crime, the introduction of Justice Collaborators has become a pivotal component in the criminal justice system. This study explores the concept of Justice Collaborators, their roles, legal protections, and the impact of their participation in legal proceedings. Utilizing a qualitative approach, the research analyzes various legal documents, court decisions, and statutory provisions related to Justice Collaborators in Indonesia. The findings indicate that Justice Collaborators play a crucial role in unveiling complex criminal activities and assisting law enforcement in investigation and prosecution. The study also highlights the legal and physical protections offered to these individuals, emphasizing their importance in dismantling organized crime networks. The implications of these findings suggest a need for further refinement in legal provisions concerning the selection and protection of Justice Collaborators, ensuring their effective utilization in the judicial process.Highlights: Justice Collaborators are instrumental in uncovering complex criminal activities, particularly in organized narcotics crime. The legal system provides both physical and legal protections to Justice Collaborators, ensuring their safety and cooperation. The involvement of Justice Collaborators necessitates ongoing refinement in legal provisions for their selection, protection, and use in legal processes. Keywords: Justice Collaborators, Narcotics Crimes, Legal System, Organized Crime, Law Enforcement